2022
DOI: 10.4168/aair.2022.14.1.131
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IgG Anti-Thyroid Autoantibodies in Chinese Patients With Chronic Spontaneous Urticaria and a Literature Review

Abstract: Immunoglobulin (Ig) E and IgG anti-thyroid autoantibodies (AAbs) play important roles in the immunopathogenesis of chronic spontaneous urticaria (CSU). To date, association of IgE and IgG AAbs with Chinese CSU patients has not been fully investigated. We aimed to explore prevalence rates of IgE and IgG AAbs in Chinese CSU patients and their association with clinical and laboratory parameters. Serum IgE and IgG AAbs against thyroid peroxidase (TPO) and thyroglobulin (TG), total IgE (tIgE) and specific IgEs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The reasons may include many, the most important one is that, the methodology of autoreactive IgE quantification is established only in limited urticaria centers/labs and without proper standards (e.g. recombinant IgEantiself) and references, thus discriminating CSU patients into aaCSU (auto-IgE positive) and non-aaCSU (auto-IgE negative) groups become heterogeneous in different studies, making the corresponding features of aaCSU patients in different studies sometimes become inconsistent [15,24,37 & ,41, [46][47][48]. This problem regarding auto-IgE research not only occurs in CSU but also could be observed in other auto-IgE participating diseases like bullous pemphigoid, i.e.…”
Section: Type I Autoimmune Csu and Its Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons may include many, the most important one is that, the methodology of autoreactive IgE quantification is established only in limited urticaria centers/labs and without proper standards (e.g. recombinant IgEantiself) and references, thus discriminating CSU patients into aaCSU (auto-IgE positive) and non-aaCSU (auto-IgE negative) groups become heterogeneous in different studies, making the corresponding features of aaCSU patients in different studies sometimes become inconsistent [15,24,37 & ,41, [46][47][48]. This problem regarding auto-IgE research not only occurs in CSU but also could be observed in other auto-IgE participating diseases like bullous pemphigoid, i.e.…”
Section: Type I Autoimmune Csu and Its Characteristicsmentioning
confidence: 99%
“…In 2020, Asero et al [42] documented that half of the CSU patients (10 of 20) exhibited co-occurrence of IgE and IgG antibodies targeted at least one of FceRI/FceRII/tissue factor/ thyroglobulin, and patients with both autoreactive IgE and IgG to tissue factor were having later/poorer response to omalizumab treatment compared to patients without. Subsequently, the largest multicenter study on thyroid autoimmunity in CSU as of now, which included 1100 Chinese Han adult patients with CSU in 15 study centers across China mainland, found that 23% of IgG-anti-TPO positive patients could exhibit IgE-anti-TPO positivity, and this IgG and IgE co-existence to the same target could also extend to thyroglobulin, with lower rate recorded in 12% of IgG-antithyroglobulin positive CSU patients [46]. It was also found that positive IgE-anti-TPO, positive IgG-anti-TPO, and total IgE levels below 40 kU/l served as independent predictors of antihistamine-refractory CSU, and patients with IgE-anti-TPO positivity or IgG-anti-TPO positivity exhibited significantly lower total IgE levels [46].…”
Section: What Is New About Type I Autoallergymentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, it was well known that CSU and thyroid autoimmunity often occur together, but it was unclear how the two diseases were linked mechanistically 55,56 . Since then, several studies confirmed that patients with CSU have anti-TPO IgE at varying rates up to 100% [57][58][59][60][61][62][63][64] . The reasons for the differing rates of anti-TPO IgE-positive patients across studies are currently unclear, but they likely include differences in patient populations investigated and methods used 65,66 .…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the differing rates of anti-TPO IgE-positive patients across studies are currently unclear, but they likely include differences in patient populations investigated and methods used 65,66 . Other autoantigens to which CSU patients have autoreactive IgE include double stranded DNA 67 , eosinophil cationic protein 59 , eosinophil peroxidase 59 , FcεRI 68 , interleukin-24 (IL-24) 53,69 , thyroglobulin (TG) 60,61,68,70 , tissue factor (TF) 68,70 , and transglutaminase 2 (TG2) 71 (Table 2 and Figure 2). Most of them have been reported by single studies, and further verification is needed.…”
Section: Introductionmentioning
confidence: 99%